WORD OF THE DAY ON DICTIONARY.COM: HOW FUTURE TEACHERS HELP STUDENTS’ IN VOCABULARY LEARNING? - Respati, Hastri Raras; Nur, Muhammad Rauuf Oktavian (Universitas Muhammadiyah Semarang, 2019)
As future teachers they need some methods to help learners to improve and increase their vocabulary. Besides currently future teachers will face 21st century learners. It deals with today we live in modern era. Through using of technology it could help learners on learning process. This paper studies on future teachers’ perception in order to use technology in learning process. The technology that will use is word of the day on dictionary.com application. By using the methodlearners will get new words every day.